Novel Materials-based Laser Acceleration - Deng, Huiyang; Leedle, Kenneth J.; Miao, Yu; Black, Dylan S.; Urbanek, Karel; McNeur, Joshua; Kozak, Martin; Ceballos, Andrew; Hommelhoff, Peter; Solgaard, Olav; Byer, Robert L.; Harris, James S. (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We demonstrate the first laser acceleration based on novel dielectric materials (Al2O3 and Ga2O3) with high laser damage thresholds, opening a new venue for performance optimization of dielectric laser accelerators.
CRIS-Team Scopus Importer:2021-12-24